GREEN HUMAN RESOURCE MANAGEMENT (GHRM): A REVIEW OF IMPLEMENTATION CHALLENGES - Nurul Hayani Abd Rahman; Abidah Saad; Shaira Ismail (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
Green Human Resource Management (GHRM) has emerged as a strategic framework for integrating environmental sustainability into human resource policies and practices. The evolution of GHRM demonstrates a paradigm shift from traditional HR practices to sustainability-oriented strategies, integrating green recruitment, training, and performance management. This review aims to identify the key challenges hindering its implementation across organizational contexts. Articles were selected based on their relevance to GHRM themes, such as green recruitment, training, employee engagement, and strategic integration. The review found that although GHRM practices are gaining traction, particularly in sectors aligned with global sustainability goals, several persistent challenges remain. These include financial constraints, lack of training and expertise, resistance to change and limited integration with overall business strategy. Moreover, organizations often lack reliable metrics to evaluate the effectiveness of GHRM. These findings suggest that to advance GHRM practices, organizations must adopt interdisciplinary, context-specific strategies that align HR functions with broader sustainability objectives.